2021
DOI: 10.3389/fonc.2020.612459
|View full text |Cite
|
Sign up to set email alerts
|

Changing Trends in Melanoma Incidence and Decreasing Melanoma Mortality in Hungary Between 2011 and 2019: A Nationwide Epidemiological Study

Abstract: BackgroundThe incidence of malignant melanoma has continually increased during the past few decades, however, certain reports suggest a recent change in trends. The aim of our study was to examine the epidemiology of melanoma in Hungary.MethodsThis nationwide, retrospective, longitudinal study included melanoma patients diagnosed between 1 January 2009 and 31 December 2019 using the databases of the National Health Insurance Fund (NHIF) and Central Statistical Office (CSO) of Hungary. Age-standardized incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 45 publications
6
16
0
6
Order By: Relevance
“…The mortality of melanoma showed increasing trends, similarly to incidence (6,7), however, there are regions where mortality is decreasing (8)(9)(10), including Europe (ASR per 100,000 in 2012: 3.1 for males, 1.9 for females, in 2018: 2.8 for males, 1.7 for females) (4,5). Our recent epidemiological study presented a change in Hungarian melanoma incidence trend in the last decade and confirmed a decrease in mortality, as well (11).…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…The mortality of melanoma showed increasing trends, similarly to incidence (6,7), however, there are regions where mortality is decreasing (8)(9)(10), including Europe (ASR per 100,000 in 2012: 3.1 for males, 1.9 for females, in 2018: 2.8 for males, 1.7 for females) (4,5). Our recent epidemiological study presented a change in Hungarian melanoma incidence trend in the last decade and confirmed a decrease in mortality, as well (11).…”
Section: Introductionsupporting
confidence: 73%
“…Different standardization was necessary to allow for a direct comparison with recent GLOBOCAN data that uses the ESP 1976 dataset for European analyses and to evaluate the change of melanoma MIR in recent years (ESP 2013). More details on the identification of patients with malignant melanoma were described in our previous article where we reported the main epidemiology results of our study (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, incidence rates of melanoma were documented as high as 35 cases in 100,000 in Australia and around 14 cases in 100,000 in both the USA and UK [1]. In 2019, 24 new melanoma cases per 100,000 inhabitants were diagnosed in Hungary according to the National Health Insurance Fund of Hungary (NHIF) [3]. A recent study found 2 of 13 significant changes in melanoma incidence trends in Hungary.…”
Section: Introductionmentioning
confidence: 99%
“…Between 2011 and 2015, a significant mean annual increase was detected in the overall melanoma incidence, while between 2015 and 2019, a relevant mean annual decrease was seen. The authors assumed that joining the Euromelanoma campaign supported existing Hungarian seasonal screening programs to reach a wider population leading to the decline [3].…”
Section: Introductionmentioning
confidence: 99%